2007
DOI: 10.1109/lcomm.2007.071350
|View full text |Cite
|
Sign up to set email alerts
|

On Achieving the Optimal Performance of FDL Buffers Using Burst Assembly

Abstract: This letter proposes a new dynamic burst length adjustment mechanism to achieve optimal performance of fiber delay line (FDL) buffers in optical burst switching networks. Our results show that burst blocking probability at an optical node with a fixed length FDL buffer can be kept at minimum under changing traffic conditions using the proposed mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Since the burst transmission at the cores is entirely at the optical domain and with the absence of potential optical buffers, there is a possibility of two or more bursts contend at the same outgoing channel and at the same instant. This phenomenon is There are a number of resolution mechanisms available like wavelength conversion [5], segmentation [6], optical buffering [7] and deflection routing [8].…”
Section: Fig -2: Burst Header Packet (Bhp) Formatmentioning
confidence: 99%
“…Since the burst transmission at the cores is entirely at the optical domain and with the absence of potential optical buffers, there is a possibility of two or more bursts contend at the same outgoing channel and at the same instant. This phenomenon is There are a number of resolution mechanisms available like wavelength conversion [5], segmentation [6], optical buffering [7] and deflection routing [8].…”
Section: Fig -2: Burst Header Packet (Bhp) Formatmentioning
confidence: 99%
“…Assuming that time t > 0, the arrival rate of IP packets 位 packet (t) can be changed as time goes by, and 蟻 burst (t) and D(t) can be obtained as traffic load changes. Consequently, the average burst length L burst (t) [7] can be altered by the following equation.…”
Section: Optimal Burst Length In a Single Node With Fdl Buffersmentioning
confidence: 99%
“…Extensive studies on contention resolution suggested using fiber delay line (FDL) buffer [5][6][7][8], wavelength converter (WC) [1], deflection routing [9], burst segmentation [10], burst retransmission [11], and a feedback-based contention avoidance mechanism [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure acceptable performance for Internet application services, OBS needs to overcome several roadblocks, especially including data burst contention. Extensive studies on contention resolution suggested the use of fiber delay line (FDL) buffers [5] and [6], Wavelength converters (WC) [1], deflection routing [7], burst segmentation [8], burst retransmission [9], and a feedback-based contention avoidance mechanism [10]. In spite of previous efforts to resolve the contention problem, it remained as a hurdle to guarantee quality of service (QoS).…”
Section: Introductionmentioning
confidence: 99%